2022
DOI: 10.1186/s12967-022-03491-8
|View full text |Cite
|
Sign up to set email alerts
|

Improve individual treatment by comparing treatment benefits: cancer artificial intelligence survival analysis system for cervical carcinoma

Abstract: Purpose The current study aimed to construct a novel cancer artificial intelligence survival analysis system for predicting the individual mortality risk curves for cervical carcinoma patients receiving different treatments. Methods Study dataset (n = 14,946) was downloaded from Surveillance Epidemiology and End Results database. Accelerated failure time algorithm, multi-task logistic regression algorithm, and Cox proportional hazard regression alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There has been much recent interest in the use of machine learning (ML) and different artificial intelligence algorithms for cancer predictions. Studies comparing ML with classical statistical models for risk prediction have already been published [ 29 , 30 , 31 ], and although some of the studies have demonstrated a promising path toward improved risk stratification of patients with cancer, the relevance for clinical purposes remains to be proved.…”
Section: Discussionmentioning
confidence: 99%
“…There has been much recent interest in the use of machine learning (ML) and different artificial intelligence algorithms for cancer predictions. Studies comparing ML with classical statistical models for risk prediction have already been published [ 29 , 30 , 31 ], and although some of the studies have demonstrated a promising path toward improved risk stratification of patients with cancer, the relevance for clinical purposes remains to be proved.…”
Section: Discussionmentioning
confidence: 99%
“…developed a deep learning auxiliary diagnosis based on cloud and 5 G technology to address breast cancer diagnosis in source-limited regions [ 30 ]. To evaluate the effectiveness of treatment and to predict the death risk in cervical cancer patients, analysis systems based on the multi-task logistic regression algorithm [ 31 , 32 ], the artificial fish swarm algorithm [ 33 ], and the K-means clustering and support vector machines algorithm [ 34 ] have been proposed. Compared with traditional machine learning algorithms, deep learning methods are more intelligent and suitable for complex and large data analysis.…”
Section: Introductionmentioning
confidence: 99%